Five‐year outcomes from a randomised controlled trial of a couples‐based intervention for men with localised prostate cancer. Issue 4 (18th February 2019) - Chambers, Suzanne K.; Occhipinti, Stefano; Stiller, Anna; Zajdlewicz, Leah; Nielsen, Lisa; Wittman, Daniela; Oliffe, John L.; Ralph, Nicholas; Dunn, Jeff
Abstract: Objective: Psychosexual morbidity is common after prostate cancer treatment, however, long‐term prospective research is limited. We report 5‐year outcomes from a couples‐based intervention in dyads with men treated for localised prostate cancer with surgery. Methods: A randomised controlled trial was conducted involving 189 heterosexual couples, where the man received a radical prostatectomy for prostate cancer. The trial groups were peer support vs. nurse counselling versus usual care. Primary outcomes were sexual adjustment, unmet sexual supportive care needs, masculine self‐esteem, marital satisfaction, and utilisation of erectile aids at 2‐, 3‐, 4‐ and 5‐year follow‐up. Results: The effects of the interventions varied across the primary outcomes. Partners in the peer group had higher sexual adjustment than those in the usual care and nurses group at 2 and 3 years ( P  = 0.002‐0.035). Men in usual care had lower unmet sexual supportive care needs than men in the peer and nurse groups ( P  = 0.001; P  = 0.01) at 3 years. Women in usual care had lower sexual supportive care needs than women in the peer group at 2 and 3 years ( P  = 0.038; P  = 0.001). Men in the peer and nurse group utilised sexual aids more than men in usual care; at 5 years 54% of usual care men versus 87% of men in peer support and 80% of men in the nurse group. Conclusion: Peer and nurse‐administered psychosexual interventions have potential for increasing men's adherence to treatments for erectile dysfunction. Optimal effects may be achieved through an integrated approach applying these modes of support.